2019
DOI: 10.1371/journal.pone.0222652
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure according to different types of tonometry (non-contact and Goldmann applanation) in patients with different degrees of bilateral tearing

Abstract: PurposeTo investigate intraocular pressure (IOP) readings by non-contact tonometry (NCT) and Goldmann applanation tonometry (GAT) for patients with different degrees of bilateral tearing.MethodsIn this study, we reviewed the medical charts of patients complaining of different degrees of bilateral tearing. The tear meniscus height (TMH) and IOP with NCT and GAT were measured. In each patient, a comparison of IOP readings between the eye with lower TMH and the contralateral eye with higher TMH was evaluated. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…At present, many studies have con rmed the value of TMH in the diagnosis of dry eyes, and this parameter can re ect the amount of tear secretion to some extent. Although there are some differences in the distribution range of TMH values among different populations, patients can be considered to have dry eyes when the TMH is less than 0.2 mm [21,22,23,24]. In group A, the percentage of eyes with a TMH less than 0.2 mm was 61.76% (21/34) preoperatively, 17.65% (6/34) at 1 month postoperatively, and 0 at 3 months postoperatively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…At present, many studies have con rmed the value of TMH in the diagnosis of dry eyes, and this parameter can re ect the amount of tear secretion to some extent. Although there are some differences in the distribution range of TMH values among different populations, patients can be considered to have dry eyes when the TMH is less than 0.2 mm [21,22,23,24]. In group A, the percentage of eyes with a TMH less than 0.2 mm was 61.76% (21/34) preoperatively, 17.65% (6/34) at 1 month postoperatively, and 0 at 3 months postoperatively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, a group showed that a correlation exists between the tear film thickness and the IOP measured during NCT. 60 A higher value of the tear film thickness was shown to cause higher IOP measurements. Further, in our recent study, we also deciphered the mechanism of tear film destabilization that leads to droplet generation and possibly a pathogen transmission mechanism through the corneal tear film disintegration and aerosolization.…”
Section: Introductionmentioning
confidence: 95%
“…In addition to the Goldmann applanation tonometer (GAT), which will be further discussed below, several types of tonometers are currently available, each with advantages and disadvantages [23]. The non-contact tonometry (NCT) is influenced by tear meniscus height (TMH), as the measured IOP increases with increasing tear film, and by central corneal thickness (CCT) [24][25][26]. The ocular response analyzer (ORA) uses a jet of air as the applanating force to the apex of the cornea; it can measure corneal hysteresis and the corneal resistance factor and provides higher IOP measurements as compared to GAT [27].…”
Section: Introductionmentioning
confidence: 99%